Hellboy. Masks and monsters - Mignola, Mike (Hellboy, 2010)
"Hellboy joins forces with Batman and Starman in an adventure that takes them from the rooftops of Gotham to the steamy jungles of the Amazon, to rescue the first Starman, Ted Knight, from a secret Nazi organization that plans to use him to resurrect an elder god. Next, Hellboy travels to Arcadia in search of Ghost, a spectral vigilante caught up in a web of intrigue orchestrated by an ancient mask."--Amazon.com.